The establishment of species-specific primers for the molecular identification of ten stored-product psocids based on ITS2 rDNA - Zhao, Zi-Hua; Cui, Bing-Yi; Li, Zhi-Hong; Jiang, Fan; Yang, Qian-Qian; Kučerová, Zuzana; Stejskal, Václav; Opit, George; Cao, Yang; Li, Fu-Jun (Scientific reports, 2016)
Psocids are important stored product pests found worldwide that can be spread through grain trade. Most stored-product psocids, including eggs, nymphs, and adults, are very small (~1 mm) and difficult to identify morphologically. Here, we collected 10 economically important stored-product Liposcelis spp. psocids (L. bostrychophila, L. entomophila, L. decolor, L. paeta, L. brunnea, L. corrodens, L. mendax, L. rufa, L. pearmani, and L. tricolor) from 35 geographical locations in 5 countries (China, Czech Republic, Denmark, Germany, and the United States). The ITS2 rDNA gene was extracted and sequenced. The interspecific genetic distance of the stored-product psocids was significantly higher than the intraspecific genetic distance according to the barcoding gap analysis. Ten pairs of species-specific primers based on the ITS2 rDNA were developed for psocid identification. The sensitivity estimation indicated that the species-specific primers could correctly amplify the target ITS2 gene and successfully identify psocids at 1.0 ng/mL. Additionally, these species-specific primers could quantify specificity and identify 10 stored-product psocids; this approach could also be used to accurately identify other stored-product psocids. This work provides a practical approach for the precise examination of 10 stored-product psocid species and also contributes to the development of an identification method using ITS2 rDNA.
Keywords: druhová specificita; Animals; intergenová DNA; ribozomální DNA; DNA, Intergenic; zvířata; DNA, Ribosomal; hmyz; Species Specificity; Insecta; Evolution, Molecular; molekulární evoluce